2008
DOI: 10.1007/s10393-008-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

Home Ranges of Bottlenose Dolphins (Tursiops truncatus) in the Indian River Lagoon, Florida: Environmental Correlates and Implications for Management Strategies

Abstract: Photo-identification surveys conducted between 2002 and 2005 were used to determine dolphin home ranges and site fidelity within the Indian River Lagoon (IRL), Florida. The IRL was divided into six segments based on hydrodynamics and geographic features for purposes of characterization. Among the 615 dolphins with identifiable dorsal fins, 339 had > or =6 sightings and were used in segment and linear range analyses. The majority (98%) of dolphins were seen in < or =3 consecutive segments (331/339); of these, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…Photographic evaluation has proven to be a useful tool to monitor the course of individual and population health for lacaziosis in the IRL population (Murdoch et al 2008). In our previous work, we showed that photographic assessment had a sensitivity of 75% and a specificity of 100% (Murdoch et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Photographic evaluation has proven to be a useful tool to monitor the course of individual and population health for lacaziosis in the IRL population (Murdoch et al 2008). In our previous work, we showed that photographic assessment had a sensitivity of 75% and a specificity of 100% (Murdoch et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Photo-identification methods have been described previously (Mazzoil et al 2004). We followed the classification scheme for identifying presumed evidence of lacaziosis described by Murdoch et al (2008). Briefly stated, the analysis was limited to areas of body visible during surfacing (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations